Upaya Meningkatkan Kemampuan Mengidentifikasi Alat Indera Melalui Metode Observasi Pada Siswa Kelas IV SD - Sehati, Rindu; Rambe, Titin Rahmayanti; Hilmiyatun, Hilmiyatun (Yayasan Rahmat Islamiyah, 2024)
This research aims to improve the ability of 4th grade elementary school students to identify sensory organs through the application of observation methods. The observation method is used as a learning approach that involves direct observation of the object being studied. This research involved 20 grade 4 students from SD Negeri 117856 Aek Korsik, Kualuh Hulu District, North Labuhanbatu Regency. Data was collected through pre- and post-tests, as well as observations of student learning activities. The research results showed a significant increase in students' ability to identify sensory devices after implementing the observation method. Data analysis also revealed that students showed greater interest and active involvement in learning through this method. The implications of this research highlight the importance of a learning approach based on direct experience in increasing students' understanding of abstract subject matter such as sensory systems.